Extracorporeal photopheresis in the treatment of graft-versus-host disease - I. V. Guz; P. E. Trachtman (Онкогематология)
Extracorporeal photopheresis has proved efficacy in the treatment of chronic graft-versus-host disease after allogeneic hematopoietic stem cell transplantation and is an alternative to other treatments. This method is characterized by good tolerability, the lack of age restrictions, minimum of infectious complications compared to increasing immunosuppression. This therapy gives a real improvement in the quality of life.